Effectiveness, safety and cost of drug substitution in hypertension - Johnston, Atholl (Blackwell Science Inc, 2010)
Cost-containment measures in healthcare provision include the implementation of therapeutic and generic drug substitution strategies in patients whose condition is already well controlled with pharmacotherapy. Treatment for hypertension is frequently targeted for such measures. However, drug acquisition costs are only part of the cost-effectiveness equation, and a variety of other factors need to be taken into account when assessing the impact of switching antihypertensives. From the clinical perspective, considerations include maintenance of an appropriate medication dose during the switching process; drug equivalence in terms of clinical effectiveness; and safety issues, including the diverse adverse-event profiles of available alternative drugs, differences in the ‘inactive’ components of drug formulations and the quality of generic formulations. Patients' adherence to and persistence with therapy may be negatively influenced by switching, which will also impact on treatment effectiveness. From the economic perspective, the costs that are likely to be incurred by switching antihypertensives include those for additional clinic visits and laboratory tests, and for hospitalization if required to address problems arising from adverse events or poorly controlled hypertension. Indirect costs and the impact on patients' quality of life also require assessment. Substitution strategies for antihypertensives have not been tested in large outcome trials and there is little available clinical or economic evidence on which to base decisions to switch drugs. Although the cost of treatment should always be considered, careful assessment of the human and economic costs and benefits of antihypertensive drug substitution is required before this practice is recommended.